Wyzwania cyberprzestrzeni a wybrane kompetencje nauczycieli i uczniów = Challenges in cyberspace and selected compitences of the teacher and the pupil - Popławska, Agata; Aniskievich, Tatiana (Zielona Góra: Lubuskie Towarzystwo Naukowe)
How to find one`s place in the world dominated by digital media? How to use the ensuing changes for personal development, self-fulfilment, and optimal functioning in media reality? How to deal with excessive information, a false picture of reality, homogenized cultural offer, indirectness and superficiality of social contacts, moral threats in cyberspace?
Keywords: cyberprzestrzeń; media cyfrowe; kompetencje poznawcze; kompetencje społeczne; kompetencje aksjologiczne; kompetencje informatyczne; cyberspace; digital media; cognitive competences; social competences; axiological competences; information competences